IMPROVING EMPLOYEE PERFORMANCE THROUGH LEADERSHIP STYLE AND DISCIPLINE: A STUDY ON HOTELS IN THE MANDALIKA SPECIAL ECONOMIC ZONE - Yusuf, Lalu Florian; Winarno, Alex; Fahmi, Saiful (Universitas Sang Bumi Ruwa Jurai, 2023)
This study was conducted to analyze the impact of leadership style and discipline on employee performance in Mandalika area hotels. This study was driven by the problems faced by employees in achieving their full potential, which affects company goals. The method used descriptive and causal quantitative research, using non-probability sampling with 50 respondents. The research results obtained are leadership style and discipline have a significant impact on employee performance. This study shows that leadership style and discipline can improve employee performance, which leads to better company results. The findings of this study could have significant implications for companies operating in Mandalika Special Economic Zone or similar contexts. By applying leadership style and discipline, companies can improve employee performance and achieve their goals. This study may also contribute to the existing literature on the impact of leadership style and discipline on employee performance in the hospitality industry.